Ambient Noise Levels and Wireless Headsets for Communication in Aerosolizing Otolaryngology Surgery During COVID‐19. (12th January 2021) - Levin, Marc; Zhou, Kelvin; Sommer, Ethan C.; McHugh, Tobial; Sommer, Doron D.
Abstract : The objective of this short scientific communication is to describe and test a strategy to overcome communication barriers in coronavirus disease 2019 (COVID‐19) era otolaryngology operating rooms. Thirteen endoscopic sinus surgeries, 4 skull base surgeries, and 1 tracheotomy were performed with powered air‐purifying respirators. During these surgeries, surgical team members donned headsets with microphones linked via conference call. Noise measurements and survey responses were obtained and compared to pre–COVID‐19 data. Noise was problematic and caused miscommunication as per 93% and 76% of respondents, respectively. Noise in COVID‐19 era operating rooms was significantly higher compared to pre–COVID‐19 era data (73.8 vs 70.2 decibels, P =. 04). Implementation of this headset strategy significantly improved communication. Respondents with headsets were less likely to encounter communication problems (31% vs 93%, P <. 001). Intraoperative measures to protect surgical team members during aerosolizing surgeries may impair communication. Linking team members via a conference call is a solution to improve communication.